The perception of civil service on the introduction of key performance indicators (KPI) / Amir Fahmi Abd Aziz and Nur Afzan Ab Khalid - Abd Aziz, Amir Fahmi; Ab Khalid, Nur Afzan (2010)
The Key Performance Indicators (KPIs) was introduced in the public sector through the Development Administration Circular in 2005. The performance of service delivery needs to be assessed, evaluated, monitored and improvised continuously so that the service can be delivered to customers quickly, accurately, and effectively. The main objective of KPIs are to ensure that the service delivered is of quality in line with the function, vision and mission of the agency and fulfilled the customers’ needs, Government agency needs to assess the performance of the services delivered and the outcome of the assessment on services delivered to customers will depict the overall performance of the agency. The objective of this paper is to determine the level of awareness, perception and the readiness of Civil Services in implementing the KPIs. Sixty questionnaires were distributed to four public agencies in Jerantut, Pahang. Based on the finding the level of awareness, perception on KPIs and the readiness of the public sector employees in supporting government initiative to improve their performance were identified and the papers concludes with suggestions for improvement.